'Islamophobia' and the law: Belgian hate speech legislation and the wilful destruction of the Koran. (March 2014) - Vrielink, Jogchum
In Belgium a man was convicted for incitement to racial hatred and discrimination because he publicly tore up a Koran, before the eyes of a small group of Muslims. The case fits within a wider development of increasing legal sensitivity to 'Islamophobia'. This development, however, has several problematic aspects and implications, as is illustrated by a detailed analysis of the case.